Roots of the Equation!

Algebra Level 3

Let α \alpha and β \beta be the zeros of x 2 + p x + 1 x^{2} + px + 1 .

Let γ \gamma and δ \delta be the zeros of x 2 + q x + 1 x^{2} + qx + 1 .

Find the value of ( α γ ) ( β γ ) ( α + δ ) ( β + δ ) (\alpha - \gamma) (\beta - \gamma) (\alpha + \delta) (\beta + \delta) in terms of p p and q q .

q 2 q^{2} p 2 p^{2} p 2 q 2 p^{2} - q^{2} q 2 p 2 q^{2} - p^{2}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Tom Engelsman
Mar 4, 2017

Let us write:

( x α ) ( x β ) = x 2 ( α + β ) x + α β = x 2 + p x + 1 = 0 (x-\alpha)(x-\beta) = x^2 - (\alpha + \beta)x + \alpha\beta = x^2 + px + 1 = 0

( x γ ) ( x δ ) = x 2 ( γ + δ ) x + γ δ = x 2 + q x + 1 = 0 (x-\gamma)(x-\delta) = x^2 - (\gamma + \delta)x + \gamma\delta = x^2 + qx + 1 = 0

which yields α + β = p ; γ + δ = q ; α β = γ δ = 1. \alpha + \beta = -p; \gamma + \delta = -q; \alpha\beta = \gamma\delta = 1. Now, let's expand:

( α γ ) ( β γ ) ( α + δ ) ( β + δ ) ; (\alpha-\gamma)(\beta-\gamma)(\alpha+\delta)(\beta+\delta);

or [ α β γ ( α + β ) + γ 2 ] [ α β + δ ( α + β ) + δ 2 ] ; [\alpha\beta - \gamma(\alpha+\beta) + \gamma^{2}][\alpha\beta + \delta(\alpha+\beta) + \delta^{2}]; ;

or ( 1 + p γ + γ 2 ) ( 1 p δ + δ 2 ) ; (1 + p\gamma + \gamma^{2})(1 - p\delta + \delta^{2});

or ( p γ q γ ) ( p δ q δ ) (p\gamma - q\gamma)(-p\delta - q\delta) ;

or γ ( q p ) δ ( q + p ) -\gamma(q - p) \cdot -\delta(q + p) ;

or γ δ ( q 2 p 2 ) \gamma\delta(q^2 - p^2) ;

or ( 1 ) ( q 2 p 2 ) (1)(q^2 - p^2) ;

or q 2 p 2 . \boxed{q^2 - p^2}.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...